2021
DOI: 10.1186/s40352-021-00129-7
|View full text |Cite|
|
Sign up to set email alerts
|

Undoing resilience: immigrant status and poor health following incarceration

Abstract: Background In the United States, foreign-born persons often have better health outcomes than their native-born peers, despite exposure to adversity. Nevertheless, it is unclear whether this pattern extends to the consequences of life events, such as incarceration, that separate immigrants from their supportive networks and increase exposure to adversity. Accordingly, using four waves of data from the National Longitudinal Study of Adolescent to Adult Health, hierarchical generalized linear mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Are there nativity differences in health among incarcerated individuals by race/ethnicity or citizenship status? Extant literature has established that incarceration in immigrant detention ( Saadi et al, 2022 ; Singer et al, 2022 ; Von Werthern et al, 2018 ) and correctional facilities ( Kuper & Turanovic, 2021 ) are associated with mental health, infectious disease, and/or self-rated health. We extended upon this emerging body of work to show that there are differing patterns in physical health among incarcerated and non-incarcerated populations by nativity, race/ethnicity, and citizenship status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Are there nativity differences in health among incarcerated individuals by race/ethnicity or citizenship status? Extant literature has established that incarceration in immigrant detention ( Saadi et al, 2022 ; Singer et al, 2022 ; Von Werthern et al, 2018 ) and correctional facilities ( Kuper & Turanovic, 2021 ) are associated with mental health, infectious disease, and/or self-rated health. We extended upon this emerging body of work to show that there are differing patterns in physical health among incarcerated and non-incarcerated populations by nativity, race/ethnicity, and citizenship status.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has extended this research from immigrant detention facilities to correctional facilities. Kuper and Turanovic (2021) found that although immigrants have better self-rated health overall, prior incarceration in correctional facilities erodes the self-rated health of foreign-born individuals as it does for U.S.-born individuals. Nevertheless, it is not clear if disparities in physical health exist by immigration status and race/ethnicity among incarcerated individuals.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Assimilating into a new culture offers various opportunities for growth, development, and skill‐building that can increase adaptability and resilience among immigrants (Fergus & Zimmerman, 2005; Trueba, 2002). Nonetheless, some recent work finds that the adaptability of foreign‐born persons may not be enough to protect against poor outcomes after some of the most negative life experiences (Kuper & Turanovic, 2021). Accordingly, the primary objective of this study is to examine the relationship between youth violent victimization and a host of adverse consequences in early adulthood for immigrants (i.e., poor health, depressive symptoms, low self‐esteem, suicidality, alcohol problems, drug use, property offending, and violent offending).…”
Section: Current Focusmentioning
confidence: 99%